1948
DOI: 10.1128/jb.56.6.699-708.1948
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Mutation during the Growth of Biochemical Mutants of Escherichia coli

Abstract: A bacterial culture may contain a very large number of organisms. Consequently, even mutations occurring at very low rates per organism may not be uncommon. For this reason bacterial cultures are likely to be heterogeneous and their composition will depend upon mutation rates and selection pressure (Ryan, 1948). When mutations influence the growth characteristics of bacteria, the behavior of the whole culture may be drastically influenced. In the case of the so-called biochemical mutations, which affect the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1950
1950
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…These markers were selected from a nonconjugative strain of Escherichia coli (strain 15999, American type culture collection) and have been shown to be competitively neutral with respect to one another under culture in a medium having excess histidine. The growth medium, genetic markers, and adaptation of strains have been described at length elsewhere (Ryan and Schneider 1948a, 1948b, Atwood et al 1951, Ryan and Wainwright 1954. Bacteria were stored in nutrientagar stabs, with single colony isolates used to initiate liquid cultures for experiments.…”
Section: Rand K-selection Of Experimental Strains In Batch Culturementioning
confidence: 99%
“…These markers were selected from a nonconjugative strain of Escherichia coli (strain 15999, American type culture collection) and have been shown to be competitively neutral with respect to one another under culture in a medium having excess histidine. The growth medium, genetic markers, and adaptation of strains have been described at length elsewhere (Ryan and Schneider 1948a, 1948b, Atwood et al 1951, Ryan and Wainwright 1954. Bacteria were stored in nutrientagar stabs, with single colony isolates used to initiate liquid cultures for experiments.…”
Section: Rand K-selection Of Experimental Strains In Batch Culturementioning
confidence: 99%
“…Lyophilized cells f/iysiol. I'iant, 9,1956 are however relatively easily broken in a Potter-Elvehjem homogenizer or when ground with glass powder.…”
Section: Methodsmentioning
confidence: 99%
“…The heat produced during growth may thus make temperature control critical when experiments arc Phyaiol. Plant., 9,1056 performed near the upper temperature limit of growth of au organism. Wheu the temperature was lowered to less than 25° on the other hand, hyphal growlh was favoured, aud it hecame impossible to conlinue experiments for any length of time.…”
Section: Continuous Culture Experiiueutsmentioning
confidence: 99%
“…An increase in the sugar content of the plating medium diminishes the suppresssion effect as does a decrease in the number of inhibiting auxotrophic cells present. Ryan and Schneider (1949) using K~ch. coli have shown that under anaerobic conditions the suppression of prototrophs by histidine-requiring bacteria was brought about by a somewhat similar mechanism.…”
Section: (A) the Suppression Phenomenonmentioning
confidence: 99%
“…Inhibition of protrophs by auxotrophs has been shown to occur in Esch. coli by Ryan and Schneider (1949) in studies of reversion of a histidine-dependent strain to histidine independence and in N. crussa by Grigg (1952) and Stephens and Mylroie (1953). Such inhibition may be demonstrated by plating a prototrophic and an auxotrophic strain, mixed in given proportions, on minimal medium.…”
Section: Introduotionmentioning
confidence: 99%